Buckingham’s Republic of Letters: Defining the Limits of Free Expression in British Calcutta, 1818-1832 - Scott, Logan (Université d'Ottawa / University of Ottawa, 2017)
The Marquis of Hastings’s decision in 1818 to repeal the censorship of Calcutta’s presses led many to believe the Governor General had inaugurated press freedom in Bengal, the political and intellectual centre of Britain’s Eastern Empire. With the steady inflow of non-Company merchants to India following the Charter Act of 1813, the East India Company was faced with the challenge of defending its remaining privileges, while simultaneously consolidating its newly acquired territories and developing enduring structures of governance. Building upon the work of Peter Marshall and Christopher Bayly, this thesis concentrates on the press debates of the early 1820s in order to highlight the Company’s role in preventing the emergence of an Anglo-Indian public sphere in Calcutta. Drawing on the experiences of Mirza Abu Taleb, James Silk Buckingham, and Rammohun Roy, this thesis also demonstrates the essentially transnational influences that informed these debates, while focusing on the interaction between Britons, Indians, and the Company’s military officers in Buckingham’s Calcutta Journal. It argues that despite the respective political ideologies of government officials, it was, in fact, primarily pragmatism that informed policy regarding free expression through print. In the wake of the Napoleonic and Revolutionary Wars, administrators worked to isolate and silence dissenting voices to prevent the outbreak of rebellion or independence movements, and the increasing engagement between Indians, Britons, and members of the Army proved too great a threat to Company-rule.
Keywords: India; British; Newspapers; Liberalism